1991
DOI: 10.1785/bssa0810020379
|View full text |Cite
|
Sign up to set email alerts
|

TheMLscale in Norway

Abstract: A new local magnitude ML scale has been developed for Norway, based on a regression analysis of synthesized Wood-Anderson records. The scale is applicable for distances up to more than 1000 km, and the data used comprise 741 short-period recordings at 21 seismic stations from 195 earthquakes in the magnitude range 1 to 5 occurring in and around Norway over the last 20 years. Magnitude corrections for distance have been evaluated in terms of a geometrical spreading term a and an anelastic attenuation term b, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For distances spanning up to 400 km, where our observations are present, the correction is somewhat higher compared to the eastern United States [Kim, 1998] and Norway [Alsaker et al, 1991] scales. However, for distances greater than 500 km, the correction term gradually diminishes as the distance increases, though it remains lower than that of southern California [Hutton and Boore, 1987] and central California [Bakun and Joyner, 1984], as shown in Figure 9.…”
Section: Local Magnitude Scale (M L )mentioning
confidence: 59%
See 1 more Smart Citation
“…For distances spanning up to 400 km, where our observations are present, the correction is somewhat higher compared to the eastern United States [Kim, 1998] and Norway [Alsaker et al, 1991] scales. However, for distances greater than 500 km, the correction term gradually diminishes as the distance increases, though it remains lower than that of southern California [Hutton and Boore, 1987] and central California [Bakun and Joyner, 1984], as shown in Figure 9.…”
Section: Local Magnitude Scale (M L )mentioning
confidence: 59%
“…States [Kim, 1998], and Norway [Alsaker et al, 1991] (Figure 9). It is found that the distances up to ~100 km, the present study's 𝑀 𝐿 distance correction term is larger than the southern California scale.…”
Section: Local Magnitude Scale (M L )mentioning
confidence: 99%
“…Considering the depth distribution and the small epicentral area covered, no attempt was made to subdivide the data set according to depth or epicenter. where A is peak amplitude, R is hypocentral distance in km and a and b are constants describing geometrical spreading and anelastic attenuation, the whole data base can be inverted to calculate the cons.tants a and b following the procedure used by Alsaker et al (1991). This resulted in the values a=0.4 and b=0.005 which are physically unrealistic.…”
mentioning
confidence: 99%